Pengaruh Video Advertising Tokopedia Versi â€œJadikan Ramadan Kesempatan Terbaikâ€ Terhadap Respon Afektif Khalayak - Olivia, Jennifer; Nurfebiaraning, Sylvie (LONTAR: Jurnal Ilmu Komunikasi, 2019)
Many advertisers believe that consumer emotions are better at advertising effectiveness,because if you only sell brands there will be no striking differences with competitors orcompetitors. The way to attract the consumer attentions, to use the products and brands ofthe company is to advertise and make the audience like the advertisement. One of theadvertising videos "Jadikan Ramadan Kesempatan Terbaik". Therefore, the authors wantto know and analyze a relationship, how much the relationship, influence, and how muchinfluence the Tokopedia version "Jadikan Ramadan Kesempatan Terbaik" for the affectiveresponse of audience. This research using a quantitative methods, positivistic paradigm,and analysis techniques is descriptive data analysis, and simple linier regression. Forsampling techniques was used non-probability sampling with type of incidental sampling,which is total 100 respondents. The result is a simple regression of Y = 8.091 + 0.411X.Furthermore, the correlation analysis with results of 0.657 belongs to the strong category.In this study H0 rejected and H1 accepted because tcount > ttable (8.629> 1.660) meansthat Tokopedia version "Jadikan Ramadan Kesempatan Terbaik" influences the affectiveresponse of the audience. As well as the video advertising version "Jadikan RamadanKesempatan Terbaik" affects the affective response of audiences by 43.20% while the other56.80% is influenced by other this research.